Issues for Indigenous Claims Settlement Policies Arising in Other Jurisdictions - Wickliffe, Caren (Victoria University of Wellington Law Review, 1995)
This article was developed in part from the report that the author wrote for the Parliamentary Commissioner for the Environment (Indigenous Claims and the Process of Negotiation and Settlement in Countries with Jurisdictions and Populations Comparable to New Zealand's Background, Report for the Parliamentary Commissioner's Report Environmental Information and the Adequacy of Treaty Settlement Procedures (Parliamentary Commissioner for the Environment, Wellington, 1994)). This article deals with issues raised from a consideration of other jurisdictions. The author discusses the role of commissions, tribunals and the courts, the legal and historical basis of claims, claim policies and the content of negotiations and settlements in other jurisdictions, and the content of the New Zealand Crown proposals. The author concludes that New Zealand's proposals fall well behind those developed in similar jurisdictions, despite once leading the world in its desire to address historical claims.